2019
DOI: 10.32734/ijnpc.v1i1.952
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Nasopharyngeal Carcinoma in Hassan Sadikin Hospital

Abstract: Introduction: Nasopharyngeal carcinoma (NPC) is the fifth in range of malignancies in Indonesia and has high morbidity and mortality. A survival rate is a statistical index that summarizes the probable frequency of specific outcomes for a group of patients at a particular point in time. The survival of patients with nasopharyngeal carcinoma is influenced by several factors, such as the patient and tumor. Objective: The objective of this research is to determine survival analysis and factors that influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A similar pattern is shown in America (72%, 64%, 62%, and 38%). In our center, the five-year survival rate is 30.9%, with a much lower survival rate in stage I (44.6%) [3].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…A similar pattern is shown in America (72%, 64%, 62%, and 38%). In our center, the five-year survival rate is 30.9%, with a much lower survival rate in stage I (44.6%) [3].…”
Section: Introductionmentioning
confidence: 63%
“…A previous study in our center reported that most patients with NPC mainly seek professional help due to neck lymph node metastases. The advanced stage contributes to the high mortality rate of NPC, stage III 15.4%, stage IVA 13.8%, and stage IVB 1.5% [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the study by Adriana who showed 84.9% of Stage III and IV patients, and the study in Ethiopia showed 86.2%. Studies in endemic areas show 80−90% of Stage III and IV cases [17], [18]. This could indicate the difficulty of early diagnosis due to the vague symptoms that arise in the early stages [19].…”
Section: Discussionmentioning
confidence: 99%
“…Intensive systemic treatment such as chemoradiation is needed to treat patients with NPC in Stages III and IV due to the predisposition to distant metastases as one of the primary causes of treatment failure and death in NPC patients [20]. Various studies also have shown that giving chemoradiation to NPC patients exhibits a higher survival rate than giving only radiotherapy [17], [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…8 Survival is the percentage of individuals living in a group with a certain disease in a specified period. 9 Several factors are believed to affect the survival of laryngeal carcinoma, including patient and tumor factors. 10 This study aims to show the survival of patients with laryngeal carcinoma in Indonesia.…”
Section: Introductionmentioning
confidence: 99%